Energieoptimale Längsführung von Kraftfahrzeugen durch Einsatz vorausschauender Fahrstrategien - Radke, Tobias (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2013)
The present work deals with energy-optimal longitudinal vehicle control, which incorporates predictively known route data to realise a maximally fuel-efficient driving strategy while comprising the drivers demand. To solve this optimisation problem, a resource-efficient algorithm is developed and implemented within a prototypical embedded driver assistance system for automated longitudinal control. The system achieves fuel savings of approximately 10%.